The Effect of Motivation, Leadership and Productivity on Employee Performance at PT. Perimex Desa Sukaluwei - Hepi; Ruth; Ester; Yovie Ernanda (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of motivation on employee performance at PT.Perimex, to determine the effect of leadership on employee performance at PT.Perimex, to determine the effect of productivity on employee performance at PT Perimex and to determine the effect of motivation, leadership and productivity simultaneously on employee performance at PT.Perimex. .Perimex with a population of all employees of PT. Perimex amounted to 96 people with a saturated sampling technique using total sampling, the research sample was obtained as many as 96 people. The results of the partial study obtained the t-count Motivation (X1) was 3.371 and the t-table value was 1.984 provided that the value of tcount > ttable (3.371 > 1.984) and sig value < 0.05 (0.001 < 0.05), partially obtained the t-count Leadership (X2) is 3, Leadership and Productivity make a big contribution in explaining employee performance by 76.80% while the remaining 23.20% is influenced by other factors outside the study. The conclusion of the study is that motivation has a significant effect on employee performance, leadership has a significant effect and is the dominant variable that affects employee performance, productivity has a significant effect on employee performance and simultaneously motivation, leadership and productivity have a significant effect on employee performance.